Metabolic characteristics of persons with prediabetes - Pando-Álvarez, Rosa (2024)
Objective: To study the metabolic characteristics of people with prediabetes and compare them with those of a controlgroup. Material and methods: A total of 105 people have been studied, 57 with prediabetes (prediab), 27 women and 30 men, and 48 people without prediab, 27 women and 21 men, whose anthropometric and blood measurements were taken. measured basal glucose (G0), at 60 and 120 minutes postprandial, basal (I0) and postprandial insulin (Ipp), total cholesterol (TC), HDLcholesterol (HDL), triglycerides (Tg), transaminases (TGO, TGP), vitamin D (VD), parathormone (PTH) by conventionalmethods; the HOMA index, the VLDL, LDL and NoHDL fractions were calculated. Results: People with prediab hadsignificantly higher average weight, BMI, G0, G60 and G120 than those without prediab; there were no differences in the otherbiochemical markers studied. Conclusions: People with prediabetes have a higher cardiometabolic risk than those withoutprediabetes.